Modulation of Water Exchange in Eu(III) DOTA-tetraamide Complexes: Considerations for in vivo imaging of PARACEST agents - Mani, Tomoyasu (2009)
Modulation of water exchange in lanthanide(III)-DOTA type complexes has drawn considerable attention over the past two decades particularly because of their application as contrast agents for Magnetic Resonance Imaging (MRI). LnDOTA-tetraamide complexes display unusually slow water exchange kinetics and this chemical property offers an opportunity to use these complexes as a new type of contrast agent based upon the chemical exchange saturation transfer (CEST) mechanism. Six new DOTA-tetraamide ligands having side-chain amide arms with varying hydrophobicity and polarity were prepared and the water exchange characteristic of complexes formed with europium(III) complexes were investigated. The results show that introduction of steric bulk into the amide side-chain arms of the europium(III) complexes not only favors formation of the mono-capped twisted square antiprism (TSAP) coordination isomers, the isomer that is generally less favourable for CEST, but also accelerates water exchange in the mono-capped square antiprism (SAP) isomers. However, converting single methyl groups on these bulky arms to carboxyl or carboxyl ethyl esters results in a rather dramatic decrease in water exchange rates, about 50-fold. Thus, steric bulk, polarity, hydrophobicity of the amide side-chains, each contribute to organization of water molecules in the second hydration sphere of the europium(III) ion and this in turn controls water exchange in these complexes.